2022
DOI: 10.18632/aging.204010
|View full text |Cite
|
Sign up to set email alerts
|

The role of fructose 1,6-bisphosphate-mediated glycolysis/gluconeogenesis genes in cancer prognosis

Abstract: Metabolic reprogramming and elevated glycolysis levels are associated with tumor progression. However, despite cancer cells selectively inhibiting or expressing certain metabolic enzymes, it is unclear whether differences in gene profiles influence patient outcomes. Therefore, identifying the differences in enzyme action may facilitate discovery of gene ontology variations to characterize tumors. Fructose-1,6-bisphosphate (F-1,6-BP) is an important intermediate in glucose metabolism, particularly in cancer. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In addition, studies have found that increased metabolic reprogramming and glycolysis levels are associated with tumor progression ( Li et al, 2022 ). Recent studies have shown that glycolysis/gluconeogenesis and carbon metabolism have been proven to be involved in the occurrence and development of lung cancer cells ( He et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have found that increased metabolic reprogramming and glycolysis levels are associated with tumor progression ( Li et al, 2022 ). Recent studies have shown that glycolysis/gluconeogenesis and carbon metabolism have been proven to be involved in the occurrence and development of lung cancer cells ( He et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found that increased metabolic reprogramming and glycolysis levels are associated with tumor progression ( Li et al, 2022 ). Recent studies have shown that glycolysis/gluconeogenesis and carbon metabolism have been proven to be involved in the occurrence and development of lung cancer cells ( He et al, 2022 ; Li et al, 2022 ). The tumor metabolic microenvironment plays an important role in tumor occurrence, development, invasion, and metastasis ( García-Cañaveras et al, 2019 ; Dey et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the key enzyme ALDOA (aldolase A) in glycolysis is a cancer-related gene according to the Human Protein Atlas information [ 30 ]. HIF1A was also reported to upregulate ALDOA expressions under hypoxic conditions [ 31 ]. HIF has also been shown to enhance the glucose flux in glycolysis in cancer cells to enhance energy usage [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALDOA also has non-enzymatic functions in invasive potential, drug resistance, and stem cell function of cancer cells [ 66 , 67 , 68 ]. It has been suggested that the activities of FBP1 and ALDOA are regulated by endogenous proteins during the FBP conversion [ 69 ].…”
Section: Fructose-bisphosphate Aldolase a (Aldoa) Inhibition In Cance...mentioning
confidence: 99%